The Society of Surgery of Uruguay and the French surgical school. A centenary bond. - Ruso Martínez, Luis (Cirugía del Uruguay, 2022)
The history of surgery and surgical schools were built on the basis of medical knowledge, but also influenced by the great currents of political, religious, cultural and even military thought of the different times. The influence of the French surgical school in the development of surgery in Uruguay, for more than a century, has been decisive in establishing its pillars: clinical evidence, expertise in anatomy, technical excellence, a permanent critical analysis for promote the generation of knowledge; based on ethics principles of respect for the patient and his suffering. The present study analyzes, from the perspective of the general surgery, the first surgical contacts during the first civil war, the beginning of the academic training of Uruguayan surgeons in France, the technical aspects and the relevant publications resulting from these experiences; as well as anecdotes and personal and institutional friendships on which a solid model of scientific relationship was built, especially through the Uruguay Society of Surgery.